A Comparative Study of Xi's Tendon Gangrene (Nonischemic Type of Diabetic Foot) and Gangrene (Diabetic Foot Ischemic Type). (28th June 2022) - Peng, Linfeng; Wang, Yuzheng; Zhao, Cheng; Zhao, Zhiguo; Fei, Qi; Xin, Pengchao; Xu, Hongtao; Cao, Yemin
Abstract : Background . Diabetic foot gangrene refers to a lesion in which the tissue of the foot or lower extremities of diabetic patients is damaged, and the cause is the infection of peripheral blood vessels and neuropathy caused by diabetes. Objective . To compare the related indexes of blood glucose, inflammation, blood viscosity, and peripheral neuropathy between the nonischemic diabetic foot and ischemic diabetic foot, the same and different characteristics of the two different types of diabetic foot in pathogenesis were discussed and studied. Methods . A total of 122 patients with diabetic foot were selected from the Department of Vascular Medicine, Shanghai Hospital of Integrated Traditional Chinese and Western Medicine, including 61 cases of ischemic type and 61 cases of nonischemic type. The differences in blood glucose, inflammation, blood supply, and peripheral neuropathy between the nonischemic diabetic foot and ischemic diabetic foot were compared to explore their different characteristics. Results . The blood glucose index, inflammatory index, and plasma fibrinogen in patients with nonischemic diabetic foot were significantly higher than those in patients with ischemic diabetic foot (P < 0.05 ). The patients with ischemic diabetic foot were higher in age and blood lipid index than those with the nonischemic diabetic foot (P < 0.05 ), while having no significant difference in platelet count, plasma viscosity, hematocrit, and end products of glycation (AGEs). Conclusion . The nonischemic diabetic foot is mainly infective necrosis, and the ischemic type is ischemic necrosis. The former occurs in the middle-aged and elderly with good blood supply between 40 and 60 years old, while the latter occurs in the elderly with the severe vascular disease over 60 years old. The blood glucose level of nonischemic patients is significantly higher than that of ischemic patients, but it has little to do with the course of diabetes.